2021
DOI: 10.4038/jas.v16i1.9182
|View full text |Cite
|
Sign up to set email alerts
|

Root System Architecture and nitrogen Uptake Efficiency of Wheat Species

Abstract: Purpose : Plant nitrogen use efficiency can be increased by improving N uptake efficiency (NUpE). Root system architecture of the plant plays a vital role in uptaking water and nutrients including N. The present study was conducted to compare root architectural traits of different wheat species at early seedling development and vegetative growth stage while plant nitrogen uptake at vegetative and mature stages under controlled environment.Research Method : Ten genotypes belong to four wheat species; einkorn, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…At maturity, spelt produced 59% and 67% of greater root length than bread wheat and emmer, respectively. Fernando et al (2021) found that two weeks old seedlings of emmer had wider emergence angles and tip angles in seminal roots than spelt, bread wheat and einkorn. According to the results of the present study, emmer genotypes developed shallow root systems at maturity.…”
Section: Total Root Lengthmentioning
confidence: 91%
See 1 more Smart Citation
“…At maturity, spelt produced 59% and 67% of greater root length than bread wheat and emmer, respectively. Fernando et al (2021) found that two weeks old seedlings of emmer had wider emergence angles and tip angles in seminal roots than spelt, bread wheat and einkorn. According to the results of the present study, emmer genotypes developed shallow root systems at maturity.…”
Section: Total Root Lengthmentioning
confidence: 91%
“…After that, WinRHIZO regular V.2002c software was used to analyse all scanned root images (Fig. 4C) (Fernando et al 2021). Following scanning, roots together with shoots were oven-dried at 80 o C for 48 hours before determining their dry weight.…”
Section: Root Screeningmentioning
confidence: 99%
“…From April to June, the nitrogen removal rate increased rapidly with increases in temperature. This was because appropriate high temperatures facilitate the microbial nitrification and denitrification reactions for removing nitrogen from the ditches [32]. From June to August, the purification rate of plants and microorganisms showed an oscillating trend with increases in temperature, which was due to the sensitivity of plants and microbial growth to external factors [32,33].…”
Section: Variation In Nitrogen In the Sedimentmentioning
confidence: 99%
“…This was because appropriate high temperatures facilitate the microbial nitrification and denitrification reactions for removing nitrogen from the ditches [32]. From June to August, the purification rate of plants and microorganisms showed an oscillating trend with increases in temperature, which was due to the sensitivity of plants and microbial growth to external factors [32,33]. At high temperatures, the growth of plants, as well as the nitrification and denitrification of microorganisms were inhibited to a certain extent, thereby decreasing the nitrogen removal rate; moreover, the microbial population may reach a peak at this time due to the nutrients in the substrate that may not be sufficient to sustain the growth of the population, leading to a dynamic equilibrium [34,35].…”
Section: Variation In Nitrogen In the Sedimentmentioning
confidence: 99%